Adaptation of the Conditions For Work Effectiveness Questionnaire II amongst Polish nurses and midwives - Agnieszka Orłowska; Mariola Łaguna (Nofer Institute of Occupational Medicine, 2018)
Background The article presents the Polish adaptation of the Conditions for Work Effectiveness Questionnaire II (CWEQ II), developed by Laschinger et al. The Conditions for Work Effectiveness Questionnaire II measures structural empowerment and is widely used in the research conducted among nurses and midwives. Structural empowerment is the ability to mobilize all available opportunities, information, resources and support in an organization. It refers to creating conditions which allow for individual development and provide access to decision-making processes. The aim of the study was to test psychometric properties of the Polish version of the CWEQ II and to verify the factor structure of structural empowerment in the Polish sample. Material and Methods The participants were 279 nurses and midwives employed in hospitals and clinics. Items were translated from the original English version using the back-translation method. Results The confirmatory factor analysis confirmed the best fit of the 6-factor model. The scales exhibit high internal consistency and satisfactory validity. Conclusions In effect of the study, the Polish adaptation of the tool has been obtained, which shows satisfactory psychometric properties, suitable for evaluation of the level of empowerment in the case of nurses and midwives. Med Pr 2018;69(5):547-560